Relationship between motor performance and cortical activity of older neurological disorder patients with dyskinesia using fNIRS: A systematic review - Wu, Yunzhi; Dong, Yuqi; Tang, Yunqi; Wang, Weiran; Bo, Yulong; Zhang, Cui (Frontiers in Physiology, 2023)
Background: Neurological disorders with dyskinesia would seriously affect older people’s daily activities, which is not only associated with the degeneration or injury of the musculoskeletal or the nervous system but also associated with complex linkage between them. This study aims to review the relationship between motor performance and cortical activity of typical older neurological disorder patients with dyskinesia during walking and balance tasks. Methods: Scopus, PubMed, and Web of Science databases were searched. Articles that described gait or balance performance and cortical activity of older Parkinson’s disease, multiple sclerosis, and stroke patients using functional near-infrared spectroscopy were screened by the reviewers. A total of 23 full-text articles were included for review, following an initial yield of 377 studies. Results: Participants were mostly PD patients, PFC was the favorite region of interest, and walking was the most popular test motor task, interventional studies were four. Seven studies used statistical methods to interpret the relationship between motor performance and cortical activation. The motor performance and cortical activation were simultaneously affected under difficult walking and balance task conditions. The concurrent changes of motor performance and cortical activation in reviewed studies contained the same direction change and different direction change. Conclusion: Most of the reviewed studies reported poor motor performance and increased cortical activation of PD, stroke and MS older patients. The external motor performance such as step speed were analyzed only. The design and results were not comprehensive and profound. More than five weeks walking training or physiotherapy can contribute to motor function promotion as well as cortices activation of PD and stroke patients. Thus, further study is needed for more statistical analysis on the relationship between motor performance and activation of the motor-related cortex. More different type and program sports training intervention studies are needed to perform.